A quantitative model for oxygen uptake and release in a family of hemeproteins - Bustamante, Juan Pablo (2016)
Motivation: Hemeproteins have many diverse functions that largely depend on the rate at which they uptake or release small ligands, like oxygen. These proteins have been extensively studied using either simulations or experiments, albeit only qualitatively and one or two proteins at a time. Results: We present a physical-chemical model, which uses data obtained exclusively from computer simulations, to describe the uptake and release of oxygen in a family of hemeproteins, called truncated hemoglobins (trHbs). Through a rigorous statistical analysis we demonstrate that our model successfully recaptures all the reported experimental oxygen association and dissociation kinetic rate constants, thus allowing us to establish the key factors that determine the rates at which these hemeproteins uptake and release oxygen. We found that internal tunnels as well as the distal site water molecules control ligand uptake, whereas oxygen stabilization by distal site residues controls ligand release. Because these rates largely determine the functions of these hemeproteins, these approaches will also be important tools in characterizing the trHbs members with unknown functions.